Augmenting Learning with Augmented Reality: Exploring the Affordances of AR in Supporting Mastery of Complex Psychomotor Tasks - Yoo, Dong Woo; Reza, Sakib; Wilson, Nicholas; Jona, Kemi; Moghaddam, Mohsen (2023)
This research seeks to explore how Augmented Reality (AR) can support learning psychomotor tasks that involve complex manipulation and reasoning processes. The AR prototype was created using Unity and used on HoloLens 2 headsets. Here, we explore the potential of AR as a training or assistive tool for spatial tasks and the need for intelligent mechanisms to enable adaptive and personalized interactions between learners and AR. The paper discusses how integrating AR with Artificial Intelligence (AI) can adaptably scaffold the learning of complex tasks to accelerate the development of expertise in psychomotor domains.